Improving Student Learning Outcomes Through The Wordwall-Assisted Problem Based Learning Model on The Human Digestive Organs - Nisa, Fitriyatun; Rochmah, Eliya; Putra, Nugraha Permana (Jurnal Ilmiah Global Education, 2025)
This study aims to improve student learning outcomes through the application of problem-based learning models assisted by wordwall media on the material of human digestive organs in grade V of SDN 2 Lemah Mekar. The method used is classroom action research (CAR) through two cycles. Each cycle consists of the stages of digestion, implementation, observation and reflection. The results of the study showed an increase in learning outcomes from the pre-cycle with a percentage of 31% increasing to 61.54% in cycle I and reaching 92.31% in cycle II. The problem-based learning model provides opportunities for students to be active in solving problems and discussing, while the wordwall media makes learning more interesting and interactive. Thus, the application of the problem-based learning model assisted by wordwall media is proven to be effective in improving student learning outcomes on the material of human digestive organs.